Agencies and Mechanisms of Social Inclusion and Exclusion Among People Living with HIV/AIDS in Mizoram. Issue 2 (December 2021) - Khawlhring, Lalrempui; Sangpui, Lily; Easwaran, Kanagaraj
The association of human immunodeficiency virus infection and acquired immunodeficiency syndrome (HIV/AIDS) with stigma and discrimination remain a challenge in combating HIV/AIDS. It pushes people to remain hidden with the potential to manifest in the future. This study aims to examine the agencies and mechanisms of social inclusion and exclusion among people living with HIV/AIDS (PLWHA) in the state of Mizoram. The study covers two districts of Mizoram, Lunglei and Saiha districts, selected purposively. Respondents were identified through different gateways like non-governmental organisations (NGOs) and hospital. A total of sixty respondents were interviewed, thirty respondents from each district selected proportionately. The study reveals that the same agencies which cater to the inclusion of PLWHA can also exclude them through different mechanisms. Agencies at primary and secondary level adopted a mixture of both inclusionary and exclusionary measures. At tertiary level NGOs, hospitals staff are seen to be more inclusionary than social institutions such as the church and youth associations. The study highlights the need for greater awareness on HIV/AIDS at the individual and community level.